2014
DOI: 10.1111/gwat.12310
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Recharge Estimation Methods During a Wet Period in a Karst Aquifer

Abstract: Management of water resources, implying their appropriate protection, calls for a sound evaluation of recharge. Such assessment is very complex in karst aquifers. Most methods are developed for application to detrital aquifers, without taking into account the extraordinary heterogeneity of porosity and permeability of karst systems. It is commonly recommended to estimate recharge using multiple methods; however, differences inherent to the diverse methods make it difficult to clarify the accuracy of each resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…For these reasons, choosing the most appropriate method for quantifying groundwater recharge and development depends on the conceptual model of the study area (Scanlon et al 2002). Experience has shown that confidence in recharge assessment improves when applying a combination of different methods consistent with the conceptual model of recharge (Beekman and Xu 2003;Scanlon et al 2002;MartosRosillo et al 2013;Guardiola-Albert et al 2014). However, in some cases the results of the methods are quite different; thus, the use of various methods shows the level of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these reasons, choosing the most appropriate method for quantifying groundwater recharge and development depends on the conceptual model of the study area (Scanlon et al 2002). Experience has shown that confidence in recharge assessment improves when applying a combination of different methods consistent with the conceptual model of recharge (Beekman and Xu 2003;Scanlon et al 2002;MartosRosillo et al 2013;Guardiola-Albert et al 2014). However, in some cases the results of the methods are quite different; thus, the use of various methods shows the level of uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…This method has been recently applied in continental Spain (Alcalá and Custodio 2014) and especially in carbonate aquifers of the Betic Cordillera (Andreu et al 2011;Alcalá et al 2011;MartosRosillo et al 2013;Guardiola-Albert et al 2014). In some carbonate aquifers featuring watersheds with gaining stream (ITGE-COPTJA 1998), groundwater recharge has been evaluated by hydrograph separation (baseflow) and empirical approaches such as the method of Kessler (1965).…”
Section: Environ Earth Scimentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, calculation of recharge through conventional methods (evapotranspiration, natural, chemical or synthetic isotopic tracing, and calculation of precipitation against time) or through numerical models has limitations such as lack of access to accurate and periodic data (Radulovic et al 2012). In the area under study, due to the lack of periodic assessment of the discharge of large springs, such methods produce limitations and problems in calculation of recharge (Guardiola-Albert et al 2015). Recent years showed significant improvements in assessment methods which are in direct relation to GIS software and many researchers have used these methods (Jyrkama & Sykes 2007;Scibek & Allen 2006;Marechal et al 2006;Lee et al 2006;Samper et al 2005;Conrad et al 2004;Tapia Silva & Mora Flores 2004;Peña & Arcos 2004;Bouraoui et al 1998;Burke 1995).…”
Section: Hossein Alem Akbar Esmaeilzadeh Soudejani and Saba Nahas Farmmentioning
confidence: 99%
“…According to the possibility of mapping, the spatial distribution of recharge rate inside aquifers is consistent with their individual features, and especially when focusing on carbonate aquifers, the APLIS method was preferred. The application of this technique has been successful in a vast number of Spanish karst aquifers (Andreo et al 2007;Martos-Rosillo et al 2009;Andreu et al 2011;Guardiola-Albert et al 2015). Furthermore, the application of APLIS method in karst aquifers has been made possible in a number of countries (Farfan et al 2010;Gerner et al 2012).…”
Section: Introductionmentioning
confidence: 99%